STRATEGI PENINGKATAN NILAI TAMBAH (VALUE ADDED) EKOWISATA PADA MASYARAKAT PESERTA HUTAN KEMITRAAN DI DESA TIWINGAN LAMA KECAMATAN ARANIO - Tampubolon, Waldy Samuel Payaman; Achmad, Basir; Satriadi, Trisnu; Abidin, Zainal (EnviroScienteae, 2024)
Strategies to ensure the sustainability of forest functions require policies that support forest management through partnership programs. Forest Farmers Group (KTH) Alimpung in Tiwingan Lama Village, Banjar Regency, is engaged in Agroforestry, Silvopastural, and Development of Non-Timber Forest Products in the Sultan Adam Forest Park. Stipulated by Decree No. 10 of 2019, they manage 371 ha with a forestry partnership scheme, focusing on ironwood plants, rubber, and the Bukit Alimpung tourist attraction. This study identifies problems and increases the added value of ecotourism businesses participating in the Partnership Forest Program in Tiwingan Lama Village, Aranio District. Through SOAR analysis, this study provides concrete strategies to strengthen the ecotourism of local communities to be more independent and prosperous. The main goal is to find out the added value of the ecotourism business of the program participants. This study collected data from KTH Alimpung through interviews, direct observations, and secondary data from related agencies and scientific literature. A mixed descriptive and quantitative approach was used with a case study on KTH Alimpung, involving 30 respondents with proportional sampling techniques. The value-added analysis and SOAR were carried out to better understand the activities and Aspirations of KTH Alimpung in forest management and ecotourism development. The ratio of added value of ecotourism businesses reached 87.44%, indicating high productivity and economic value. New strategies from SOAR's analysis for the development of ecotourism businesses participating in partnership forests include: S-A (improvement of transportation, facilities/infrastructure, and tourism management with the government), O-A (optimization through social media and government support for the development of ecotourism spots), S-R (provision of transportation, free public facilities, and addition of tourist spots), and O-R (promotion through social media to increase revenue with cost-efficiency).